Kecerdasan Emosi, Kedisiplinan Dan Kecemasan Siswa Bintara Kowal Dalam Menjalani Pendidikan Dasar Militer TNI-AL - Tjahjaningrum, Tennyn (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract : The aims of this research to examine the relations among the emotional quotient, discipline and anxiety. The subject of this study were 40 students of woman petty officer â€œDikmabawan TNI AL XXXIâ€ academic year 2012. Data were collected by scales of anxiety, emotional quotient and discipline. Based on the correlation and the regression analyses were obtained there was no correlation among the discipline with anxietyâ€™s student of woman petty officer in facing the basic military education of the Indonesian Naval. ExpectionallyÂ  emotional quotient with anxiety showed a negative correlation signifycantly.Â  The more emotional quotient, the less anxiety. Nevertheless the result of correlation analyses between either emotional quotient or discipline have a significant relation with anxiety. Variables of emotional quotient and discipline give effective contribution toward anxiety about 52.6%.Keyword :, Anxiety, Emotional Quotient And Discipline.